Asupan Gizi Makro dan Durasi Tidur pada Remaja Usia 16-18 Tahun dan Hubungannya terhadap Lama Menstruasi - Lilia Faridatul Fauziah; Diffah Hanim; Eti Poncorini Pamungkasari (Media Kesehatan Masyarakat Indonesia, 2019)
Factors influence variations in adolescent menstrual duration would change the hormonal rhythm of thehypothalamic-pituitary-ovarian cycle, so that it indirectly changes the level of secretion of the reproductive hormones.Nutritional intake is predicted to be one of the factors in the regulation of reproductive hormones, as wellas the sleep and wake cycles in a teenager. This study analyzed the relationship between macro nutrient intake andsleep duration with menstrual duration in adolescents aged 16-18 years. 120 adolescents was selected by usingcluster random sampling from 6 high schools in Magelang City-Central Java for this cross sectional study. Allof variable were collected through interview techniques using a questionnaire. Analysis with correlation test andmultiple linear regression used to analyze the relationship between each independent variable with the dependentvariable with a significance value <0.05 and the relationship of all independent variables on the dependent variable.The correlation (Pearson correlation test) between energy intake(r=0.397:p=0.000), fat(r=0.396:p=0.000),carbohydrate(r=0.337:p=0.000), and sleep duration(r=0.315:p=0.000) with menstrual duration was significant,whereas for protein intake (Spearman Rank test) was not significantly associated (r=0.018:p=0.841). The value ofR2 = 0.252.Based on this, it is important to regulate macro nutrient intake and sleep duration for having normalmenstrual duration.